Enhanced ferro magnetism of (Cu, Fe/Mn) dual doped ZnO nanoparticles and assessment of in-vitro cytotoxicity and antimicrobial activity for magnetically guided immunotherapy and hyperthermia applications. (November 2022) - Muthusamy, C.; Ashokkumar, M.; Boopathyraja, A.; Priya, Veeraraghavan Vishnu
Abstract: Cu and Fe/Mn dual doped ZnO magnetic nanoparticles (MNPs) had been synthesized by sol-gel method. Characterization of synthesized MNPs showed the fine and significant size of MNPs, it had ferromagnetism property at room temperature, and (Cu, Fe) dual doped MNPs were found to have maximum saturation magnetization with larger hysteresis area. In-vitro cytotoxic assessment of these MNPs revealed that 20 ng of Cu doped ZnO MNPs are nontoxic to human PBMC with 60% viable cell count, whereas Fe dopant increases cell viability by 5% in the same concentration. These MNPs showed a significant (20–25 mm ZOI) antimicrobial activity against Pseudomonas putida and Bacillus subtilis bacteria. Particularly Fe dopant showed increased antimicrobial activity against gram-positive ( B. subtilis ), whereas Mn dopant doesn't have considerable antimicrobial activity. Having known that these MNPs are biocompatible with the ferromagnetic property they may be considered for magnetic guided immunotherapy and hyperthermia applications. Highlights: All the NPs had ferromagnetic nature at room temperature. The hysteresis loss was high for Cu, Fe co-doped magnetic nanoparticles (MNPs). The In-vitro cytotoxicity had been reduced by Fe dopant. The cytotoxicity of MNPs is Dosage independent. Suitable candidate materials for magnetic hyperthermia applications.